Risks of the Athletic Field Revisited: Report of Unusual Occurrences of Cardiac Arrest and Sudden Death in Professional Soccer Players - Bonaventura, Jiri; Rowin, Ethan J; Maron, Martin S; Maron, Barry J (The American journal of medicine, 2023)
BACKGROUND: Sudden deaths in competitive athletes are highly visible but potentially preventable events that generate great interest amongst the cardiovascular community and general public. METHODS: Internet searches were performed using a combination of keywords and operators to produce search results for sudden death or cardiac arrest on the field in professional soccer players. RESULTS: We identified 35 male professional soccer players (mean age 26 ± 5 years) who experienced collapse and cardiac arrest on the field (most during matches) in Europe from December 2002 to February 2022 with 63% in the last 6 years. Twenty-five have died on the field or later in a hospital despite cardiopulmonary resuscitation. Of the 10 survivors, eight were implanted with cardioverter-defibrillators for secondary (n = 6) or primary (n = 2) prevention and returned to full competition; five of the 8 required successful device therapy during matches or training. CONCLUSIONS: Cardiac arrest and sudden death can occur not uncommonly in professional athletes highly trained over decades and participating at an elite sports level. Our observations also underscore the importance of targeted preparticipation cardiovascular screening, and availability of external defibrillators on the playing field.
Keywords: fotbal; Soccer; Heart Arrest; sportovci; srdeční zástava; náhlá srdeční smrt; Cardiopulmonary Resuscitation; mužské pohlaví; Adult; mladý dospělý; Athletes; sporty; kardiopulmonální resuscitace; Young Adult; Humans; Sudden death; Death, Sudden, Cardiac; dospělí; Sports; lidé; Male